Discovery of novel jaspine B analogues as autophagy inducer. Issue 3 (1st February 2018) - Zhang, En; Wang, Shang; Li, Li-Li; Hua, Yong-Gang; Yue, Jing-Fei; Li, Jin-Feng; Jin, Cheng-Yun
Graphical abstract: Abstract: A series of 2-alkylaminomethyl jaspine B analogues were synthesized and evaluated for their cytotoxic effects on human lung adenocarcinoma, breast cancer, and prostate cancer cell lines and a mouse melanoma cell line. Most of the compounds exhibited moderate to good activity against the cancer cell lines. Compound7f showed the best overall cytotoxicity on PC-3 cells (IC50  = 0.85 μM). Further mechanistic studies revealed that compound7f induced marked changes in PC-3 cell morphology, disrupted the mitochondrial membrane potential, and increased expression of the autophagy proteins beclin-1, LC3, and P62.